Assessment of Haematological Parameters in Drug-Resistant TB - Abdulrazzaq Neamah Zghair (Journal of Techniques)
Mycobacterium tuberculosis causes tuberculosis (TB), the world's deadliest infectious illness. In addition to the lungs, bone marrow is also impacted by tuberculosis. Significant haematological abnormalities can be found in TB patients. This means that these haematological markers can be used to assess a patient's diagnosis, prognosis, and treatment outcome. The goals of this study are (a) to assess the hematological characteristics of TB patients, and (b) to examine the impact of rifampin (RIF) resistance on the prevalence of mutations in the whole rpoB gene of Mycobacterium tuberculosis. Fifty people participated in the study after being chosen through a systematic random sample process. From each participant, about 4 milliliters of blood were taken from a vein and estimated for the haematological parameters like Hb, WBC, Lymphocyes, neutrophils, Erythrocyte sedimentation rate and platelet count.  Fifty tuberculosis isolates had their whole rpoB genes sequenced so that we could analyze the positions of the codons and the frequency with which they occurred. When compared to healthy controls, the values of hemoglobin and other blood indices were significantly lower or abnormal (p<0.05). ESR values were alarmingly increased in the subjects along with platelets (P value < 0.05).  All of our 25 isolates exhibited four types of mutations at four RRDR positions (codons 510, 516, 522 and 526). We found codons 526 showed a high level (92%) of RIF resistance or mutations when compared to other positions. An easy and affordable way to forecast the progression of the illness and keep track of complications in underdeveloped nations is to test the haematological parameters of tuberculosis patients. RIF resistance is linked to certain mutations in the rpoB gene that may impact how RpoB and RIF interact. These results may be used to create new antibiotics and create cutting-edge diagnostic tools for TB medication resistance.